Comment on "Uncommon structural and bonding properties in Ag16B4O10" by A. Kovalevskiy, C. Yin, J. Nuss, U. Wedig, and M. Jansen, Chem. Sci., 2020, 11, 962. Issue 40 (5th October 2021) - Lobato, A.; Salvadó, Miguel A.; Recio, J. Manuel
Abstract : ELF superbasins (dark-yellow stick and ball circuits) reveal how borate clusters (green and red spheres) play the role of crystal defects interrupting the electric conductivity of metallic silver (grey spheres). Abstract : A thorough systematic study of the Electron Localization Function (ELF) in fcc silver metal, the deficient vacant-type Ag16 □4 structure, and the Ag16 B4 O10 title compound of the Chem. Sci., 2020, 11, 962 edge article leads to a further understanding of the sub-valent characteristics of silver in the silver borate compound. By visualizing the process in three consecutive steps, (fcc)eq -Ag → (fcc)ex -Ag → Ag16 □4 → Ag16 B4 O10, the electron reduction of Ag atoms can be traced to be due to (i) the expansion (ex) of the host metallic array from its equilibrium (eq) geometry and (ii) the vacancy creation and subsequent insertion of guest borate clusters. Our ELF analysis also allows us to identify to what extent metallic features remain in the title compound, providing an alternative explanation of why Ag16 B4 O10 is not a conductor whereas pure silver is.